2019
DOI: 10.1002/asl.888
|View full text |Cite
|
Sign up to set email alerts
|

Modeled changes to the Great Plains low‐level jet under a realistic irrigation application

Abstract: Low‐level jets (LLJs) are relatively fast‐moving streams of air that form in the lower troposphere and are a common phenomenon across the Great Plains (GP) of the United States. LLJs play an important role in moisture transport and the development of nocturnal convection in the spring and summer. Alterations to surface moisture and energy fluxes can influence the planetary boundary layer (PBL) development and thus LLJs. One important anthropogenic process that has been shown to affect the surface energy budget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Following [3] and [14], a LLJ in this study is identified if the simulated vertical wind profile at a particular grid point meets the following two criteria: (1) A wind speed maximum no less than 12 m s −1 must be present below 3000 m above ground level (AGL) and (2) the decrease of wind speed from the maximum to the next minimum above (or 5000 m AGL, whichever is lower) and below (or surface, whichever is higher) must be no less than 6 m s −1 . These criteria are applied at every surface grid point in the domain and at all the 3-hourly model output times.…”
Section: Low-level Jet Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Following [3] and [14], a LLJ in this study is identified if the simulated vertical wind profile at a particular grid point meets the following two criteria: (1) A wind speed maximum no less than 12 m s −1 must be present below 3000 m above ground level (AGL) and (2) the decrease of wind speed from the maximum to the next minimum above (or 5000 m AGL, whichever is lower) and below (or surface, whichever is higher) must be no less than 6 m s −1 . These criteria are applied at every surface grid point in the domain and at all the 3-hourly model output times.…”
Section: Low-level Jet Identificationmentioning
confidence: 99%
“…Parish and Oolman [13] used the Weather Research and Forecasting Nonhydrostatic Mesoscale Model (WRF-NMM) to examine the importance of topography on LLJ formation and found that heating over sloping terrain leads to stronger background geostrophic flow that contributes to maximum simulated LLJs over the Great Plains through the inertial oscillation mechanism following the decoupling of the frictional layer from the free atmosphere above. Recently, Arcand et al [14] employed the WRF model to investigate how irrigation, a common practice in the southern Great Plains, may affect LLJ properties and identified changes in LLJ characteristics over and especially downstream of heavily irrigated regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite considerable work by previous studies, there remain gaps in understanding the interactions between irrigation and mesoscale circulations such as the slope wind. Most studies that address the effects of irrigation (and soil moisture) on mesoscale circulations are theoretical in nature or utilize relatively coarse analysis grids that often poorly represent mesoscale phenomena (e.g., Anthes, 1984; Arcand et al., 2019; Campbell et al., 2019; Huber et al., 2014; Kueppers & Snyder, 2012; Ookouchi et al., 1984; Yang et al., 2020). This paper proposes to fill this gap using the extensive rawinsonde observations collected during the 2018 Great Plains Experiment (GRAINEX; Rappin et al., 2021) in Nebraska to characterize the impacts of irrigation on the Great Plains diurnal slope wind.…”
Section: Introductionmentioning
confidence: 99%
“…Improving mechanistic understanding, modeling, and forecasting of the GPLLJ has been a research priority for over half a century (e.g., Blackadar, 1957; Bonner, 1968; Du & Rotunno, 2014; Holton, 1967; Parish, 2017; Shapiro et al., 2016; Smith et al., 2019), spurred by the GPLLJ’s relevance to regional wind and water resources (e.g., Barandiaran et al., 2013; Wilczak et al., 2015), severe weather (e.g., Weaver et al., 2012), heatwaves (e.g., Thomas et al., 2020), aviation (e.g., Gultepe et al., 2019), and pollutant transport (e.g., Corsmeier et al., 1997). More recently, efforts to simulate future GPLLJ strength, northward extent, and seasonality (e.g., Tang et al., 2017; Wimhurst & Greene, 2020), including the effects of an ever‐increasing U.S. irrigation‐equipped area on the GPLLJ (e.g., Arcand et al., 2019; Yang et al., 2020), are trending.…”
Section: Introductionmentioning
confidence: 99%